2015
DOI: 10.2174/1381612821666141126100636
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intracoronary Human Umbilical Cord-Derived Mesenchymal Stem Cell Treatment for Very Old Patients with Coronary Chronic Total Occlusion

Abstract: This study aimed to investigate the safety and feasibility of intracoronary injection of human umbilical cord mesenchymal stem cell to the very old patients with coronary chronic total occlusion. 15 consecutive patients received mesenchymal stem cells from human umbilical cord in epicardial coronary artery supplying collateral circulation. The patients were randomly allocated to low-dose 3x10(6), mid-dose 4x10(6) and high-dose 5x10(6) groups. (99m)Tc single photon emission computed tomography images were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…The coronary angiograms were analyzed by two blinded coronary interventionalists and one geriatric expert. According to the guidelines of the American Society of Echocardiography, the Doppler color echocardiography images were analyzed with the synchronized surface electrocardiograms by the two blinded cardiologists and one geriatric expert …”
Section: Methodsmentioning
confidence: 99%
“…The coronary angiograms were analyzed by two blinded coronary interventionalists and one geriatric expert. According to the guidelines of the American Society of Echocardiography, the Doppler color echocardiography images were analyzed with the synchronized surface electrocardiograms by the two blinded cardiologists and one geriatric expert …”
Section: Methodsmentioning
confidence: 99%
“…Discrepancies were resolved by consensus of a third cardiologist. According to the American Society of Echocardiography Standards, a complete Doppler echocardiography study was carried out with electrocardiograms synchronized by two independent cardiologists who were blinded to the clinical trial data of all subjects as described [31]. …”
Section: Methodsmentioning
confidence: 99%
“…Our findings suggested that intracoronary infusion of human umbilical cord mesenchymal stem cells ameliorated left ventricular ejection fraction and decreased infarct size remarkably in very old patients with coronary CTO [31, 32]. However, primary percutaneous coronary intervention procedures took longer and had the risks of radiation skin injury and acute kidney injury.…”
Section: Introductionmentioning
confidence: 94%
“…[48] 2015 yılında yaptıkları bir çalımada; 15 hastaya rastgele göbek kordonundan elde edilmi MKH'leri nakletmiler ve hastaların enfarktüs alanlarında belirgin bir azalma saptarken, sol ventrikülde-ki ejeksiyon fraksiyonunun belirgin bir ekilde arttı¤ını gözlemlemilerdir. [48] Nörolojik hastalıklarda, MKH'ler özellikle omurilik yaralanmaları, MS, Parkinson ve amiyotrofik lateral skleroz (ALS) gibi hastalıkların tedavisinde ilgi çekici olmutur. Mezenkimal kök hücreler bu hastalıkların tedavisinde kullanılmakta olup, uzun dönem sonuçları beklenmektedir.…”
Section: Self-renewal (Kendini Yenileyebilme)unclassified